1962
DOI: 10.1111/j.1476-5381.1962.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTIONS OF BRETYLIUM AND GUANETHIDINE ON THE UPTAKE AND RELEASE OF [3H]‐NORADRENAUNE

Abstract: The effect of bretylium and guanethidine has been studied on the uptake and the spontaneous and reserpine-induced release of [3H]-noradrenaline in the rat heart and in the splenic nerve endings of the cat. Bretylium and guanethidine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

1963
1963
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 9 publications
2
26
1
Order By: Relevance
“…Decreased tissue uptake might therefore account for the increased amounts of adrenaline and noradrenaline found after the injection of guanethidine and bretylium, for Hertting, Axelrod & Patrick (1962) showed that in the rat bretylium and guanethidine decreased tissue uptake of [3H]-noradrenaline. Bhagat & Shideman (1963) disagree with this for bretylium but agree with the finding for guanethidine.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased tissue uptake might therefore account for the increased amounts of adrenaline and noradrenaline found after the injection of guanethidine and bretylium, for Hertting, Axelrod & Patrick (1962) showed that in the rat bretylium and guanethidine decreased tissue uptake of [3H]-noradrenaline. Bhagat & Shideman (1963) disagree with this for bretylium but agree with the finding for guanethidine.…”
Section: Discussionmentioning
confidence: 99%
“…However, intravenous infusion of norepinephrine and serotonin to reserpine pretreated rabbits did not correct the blood pressure response to ST-155. Guanethidine interferes with a release of norepinephrine from adrenergic nerve terminals due to tyramine, nerve stimulation (10) and reserpine (12). In rats the amount of norepine phrine is depleted by about 80% following pretreatment with guanethidine for 6 to 24 hours (11), whereas the amount of tissue serotonin is not depleted after 6 hours (11).,…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that sodium ions play an essential role in the uptake, retention and storage of noradrenaline in adrenergic nerve endings (Iversen & Kravitz, 1966;Gillis & Paton, 1967;Kirpekar & Wakade, 1968;Bogdanski & Brodie, 1969). The major mechanism involved in this increase in the output of noradrenaline seems to be an inhibition of the retention rather than that of the reuptake, because guanethidine, a potent inhibitor of the uptake (Hertting, Axelrod & Patrick, 1962), did not potentiate the efflux induced by low sodium. Garcia & Kirpekar (1973) demonstrated that the various procedures which are known to inhibit Na+, K+-activated ATPase or the sodium potassium pump, induce the efflux of noradrenaline.…”
Section: Resultsmentioning
confidence: 99%